HUBUNGAN LAMA MEMIMPIN DAN GAYAKEPEMIMPINAN DENGAN KONFORMITAS KELOMPOK PETERNAK KAMBING KABUPATEN BANYUMAS - Asep aziz Rahmatulloh; Krismiwati Muatip; Novie Andri Setianto (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. Based on observations that the conformity of a group is largely determined by the leader. The study aims to determine the level of group conformity, lead time and leadership style of goat breeders in Banyumas Regency, and to know the relationship between lead time and leadership style with conformity of goat breeders in Banyumas Regency. Materials and Methods. Research using survey methods. Determination of the sample area is done by purposive sampling method by taking Baturaden District, Karanglewas District and Kalibagor District. Each village was chosen one village at random, namely Suro Village, Karangsalam Village, and Tamansari Village. Furthermore, from the selected villages the farmers' groups and group members are taken as a census, so that the respondents are 55 farmers. The analysis used is Descriptive Analysis, Spearman Rank Correlation and Chi Square Analysis. Results. The results of this study indicate that group conformity is in the high category, lead time is 5-10 years and leadership style is largely democratic. Conclusion. There is a relationship between lead time and leadership style with group conformity.